(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: The aging process is marked by physiological, psychological and social changes, which affect each individual in a particular way, in a dynamic and progressive perspective. Objective: To describe the interventions performed in a support group for the elderly based on the Theory of Praxic Intervention in Nursing in Public Health. Methods: This is a qualitative study, based on the theoretical-methodological framework of the Theory of Praxic Intervention in Nursing in Public Health, with the participation of 26 elderly people, between 60 and 80 years old. The methodology was divided into five stages: capturing objective reality; interpretation of objective reality; intervention plan; interventions; reinterpretation of reality. Results: The application of the theory allowed nursing students to approach the elderly group in a broad and multidimensional way, contemplating relevant issues in gerontological assistance such as healthy eating, physical activity, life history, mental health and self-care. The main limitations were related to the physical environment and the small number of meetings. Conclusion: The nursing intervention supported by the theoretical-methodological framework triggered a process of positive transformation in the group of elderly people, as it made it possible to strengthen the role of the participants in their health-disease process and contributed to the development of the students’ skills for comprehensive care for the person elderly.